Vernacular queer and shifting power in Russia: from the late Imperial era up to the 1930s - Roldugina, I (2021)
This thesis explores the development and complexities of queer existence shown ‘from below’, that is to say, focusing on the direct speech of non-elite homosexual men and sexual and gender non-conformists from the late imperial era up to the 1930s. The current historiography of homosexuality provides a somewhat limited view, emphasizing the importance and overarching influence of medical and legal discourses on queer subjects. The thesis offers a different perspective, shifting the analysis of hegemonic discourses of experts to the self-expression of homosexuals and gender and sexual non-conformists in the tumultuous time of the 1920s. More broadly, the thesis seeks to answer the question of when a modern homosexual identity emerges not as a scientifically constructed type but as a self-accepted category. The thesis attempts to reorient our understanding of the difference between the sodomite and the homosexual, demonstrating the process of self-fashioning as a crucial element of modern sexuality. It has been previously acknowledged that the Russian Revolution of 1917 and the abrogation of the anti-sodomy article greatly influenced the understanding of homosexuality by medical professionals and triggered the proliferation of new approaches to it.